Parkett : The Parkett series with contemporary artists (Zürich : Parkett-Verlag, 2002)
Table of Content Jeff Wall looks at the Dominus Winery by Herzog & de Meuron by Kurt W. Forster John Currin Currin’s Nudes by Keith Seward Against Nature by Mark van de Walle Lots of colorful pictures in them by Sibylle Berg Laura Owens Laura Owens Paints a Picture by Russell Ferguson Monkey Man Killer by Benjamin Weissman From My Junkyard to Yours by Mungo Thomson Michael Raedecker Dirty Pictures by Bart Verschaffel No Place Like Homeless by Terry Myers Their Second Home by Dave Eggers Lou Reed, Insert Lovesickness – Dieter Roth & Dorothy Iannone by Robert Storr Teresa Hubbard & Alexander Birchler, Floating Images – Enigmatic Narratives by Konrad Bitterli Markéta Othová: Sleepwalking in Narrated Space, Les Infos du Paradis by Christina Végh Veiled Controversy, Cumulus from America by Olav Westphalen Bauhaus in the Arena, Cumulus from Europe by Thomas Hahn Weltering in Blood, Artemisia Gentileschi (1593 – 1653) by Sheena Wagstaff
﻿There is space in their pictures, not meaning the illusionism that sees the picture as a window through which we look. What John Currin, Laura Owens, and Michael Raedecker carefully conjure with every stroke of the brush is a space that breathes, a field of freedom. (editorial by publisher)
boek
Keywords: Currin, John; Raedecker, Michael; Owens, Laura